Among the braves : hope, struggle, and exile in the battle for Hong Kong and the future of global democracy - Mahtani, Shibani; McLaughlin, Timothy (Journalist) (Hachette Books, 2023)
Through the eyes of two frontline journalists comes a gripping narrative history of the Hong Kong pro-democracy movement centered around a cast of core activists, culminating in the 2019 mass protests and Beijing's brutal crackdown. Hong Kong was an experiment in governance. Handed back to China in 1997 after 156 years of British rule, it was meant to be a carve-out between hostile systems: a bridge between communism and capitalism, authoritarianism and liberal democracy. "One country, two systems" kept its media free, its courts independent and its protests boisterous, designed also to convince Taiwan of a peaceful solution to Beijing's desire for reunification. Yet this formulation excluded Hong Kong's own people, their future negotiated by political titans in faraway capitals. In 2019, an ill-conceived law spear-headed by a sycophantic leader pushed millions to take to the streets in one of the most enduring protest movements the world has ever seen. Xi Jinping responded with a draconian national security law that sought not only to end the demonstrations but quash the "problem" of Hong Kongers' identity and desire for freedom. Reverend Chu, who believed Hong Kong had to carry the spirit of students at Tiananmen Square, saw his silver-haired comrades who birthed the city's modern pro-democracy movement handcuffed and taken from their homes. Tommy, an art student radicalized into throwing Molotov cocktails, watched "braves" like him brutalized by police before his own arrest prompted him to flee. Finn epitomized the decentralized nature of the movement and its internet-fueled victories, but online anonymity couldn't stop his life from unravelling. Gwyneth could predict her eventual fate when she chose to give up her career as a journalist to stand for election as an opposition candidate, and did it anyway. In Among the Braves, Shibani Mahtani and Timothy McLaughlin tell the story of Hong Kong's past, and what the sacrifices of its people mean for global democracy's shaky foundation. -- Provided by publisher.